Plant Small Non-coding RNAs and Their Roles in Biotic Stresses - Brant, Eleanor J.; Budak, Hikmet (Frontiers in Plant Science, 2018)
Non-coding RNAs (ncRNAs) have emerged as critical components of gene regulatory networks across a plethora of plant species. In particular, the 20–30 nucleotide small non-coding RNAs (sRNAs) play important roles in mediating both developmental processes and responses to biotic stresses. Based on variation in their biogenesis pathways, a number of different sRNA classes have been identified, and their specific functions have begun to be characterized. Here, we review the current knowledge of the biogenesis of the primary sRNA classes, microRNA (miRNA) and small nuclear RNA (snRNA), and their respective secondary classes, and discuss the roles of sRNAs in plant–pathogen interactions. sRNA mobility between species is also discussed along with potential applications of sRNA–plant–pathogen interactions in crop improvement technologies.